The effectiveness of budesonide nasal irrigation in allergic rhinitis patient - Muhammad Nu'aim Ishak
Introduction: Allergic rhinitis (AR) is a long-standing disease and has been shown to cause significant impairments in patient?s quality of life. Saline nasal irrigation is a proven adjunct treatment for AR. He addition of steroid in the saline solution can provide local steroid effect and thus increase the effectiveness of this technique. Objective: Our study aimed to determine the effectiveness of budesonide nasal irrigation as an adjunct treatment for AR, compared to saline nasal irrigation. Methods: This was a randomized controlled study involving 99 patients diagnosed with AR, where half of them were treated with saline nasal irrigation and another half treated with budesonide nasal irrigation. Parameters measured include Sino-nasal Outcome Test (SNOT-22) questionnaire, endoscopic nasal examination, and blood eosinophil count. Results: Patients treated with budesonide nasal irrigation had significant improvement in all the symptoms listed in the SNOT-22 questionnaire (P<0.001) and better outcome of endoscopic nasal examination findings, especially the nasal mucosa edema and secretion (P<0.001). However, there was no significant improvement of blood eosinophil count neither for a patient treated with budesonide nasal irrigation (P=0.091) nor for patient treated with saline nasal irrigation. (P=0.527). Conclusions: Budesonide nasal irrigation is effective s as an adjunct treatment for AR compared to saline nasal douching.